Gdy słowo dzieli. Mowa pogardy i nienawiści w relacjach między ludźmi - Obrębska, Monika; Dobrowolska, Marcelina (Człowiek i Społeczeństwo, 2021)
Hate speech is defined as verbal abuse against minority groups. Its emotional basis is contempt which activates anger and revulsion. Therefore, it seems to be justified to speak of “contempt speech and hate speech” as a spreading social phenomenon, in effect resulting in a generalised deterioration in attitudes toward minorities. The media and public figures play a huge role in promoting hate speech, and it is also fostered by the sense of danger accompanying the COVID-19 pandemic. In order to stop this process, we should start to perceive hate speech as a serious social problem, the conditions and consequences of which should be the subject of reflection and scientific studies.